2013 International Conference on Manipulation, Manufacturing and Measurement on the Nanoscale 2013
DOI: 10.1109/3m-nano.2013.6737416
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of an XY positioning table

Abstract: The dynamic modeling and analysis of a novel XY positioning table are presented in this paper. The XY table is directly driven by two linear voice coil motors (LVCMs), and Xand Y-axes motion decoupling is realized by using a novel flexible decoupling mechanism. Considering the characteristics of XY table, the dynamic model of X-and Y-axes servomechanisms are established through bond graph method, respectively, and then the state space equations are derived. The result of dynamic analysis can provide important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In our previous study, we demonstrated that Schisandrin B attenuated the inspiratory and expiratory resistances in sensitized rats, and could inhibit ASMC proliferation and migration. 14 28 Zhou et al found that miR-150 promoted renal fibrosis by increasing profibrotic molecules through down-regulation of SOCS1. 29 Honda et al reported that down-regulation of miR-150 contributed to the constitutive Type I collagen overexpression in scleroderma dermal fibroblasts via the induction of integrin β3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we demonstrated that Schisandrin B attenuated the inspiratory and expiratory resistances in sensitized rats, and could inhibit ASMC proliferation and migration. 14 28 Zhou et al found that miR-150 promoted renal fibrosis by increasing profibrotic molecules through down-regulation of SOCS1. 29 Honda et al reported that down-regulation of miR-150 contributed to the constitutive Type I collagen overexpression in scleroderma dermal fibroblasts via the induction of integrin β3.…”
Section: Discussionmentioning
confidence: 99%
“…13 In 2015, Lv et al proved that Schisandrin B inhibited the proliferation of human lung adenocarcinoma A549 cells. 15 In 2016, Zhang et al 14 reported Schisandrin B could inhibit the proliferation of ASMCs. Later, Jiang et al 16 found that Schisandrin B inhibited the proliferation and invasion of glioma cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These types of machines need accurate motion control to produce high-quality products [2], [3]. Also, the high speed and high accuracy position applications have been rapidly and broadly developed to facilitate the complex automatic processes in the industrial field [4], [5]. Generally, the servomechanism systems don't have an accurate estimated parameter for friction and backlash models which leads to system uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization techniques cannot carry out it practically in real time where it takes a long time to find the optimum solution. So, we resort to the offline tuning using an accurate mathematical model for the system but, the lack of system parameters data is an obstacle to achieve this purpose [9].…”
Section: Introductionmentioning
confidence: 99%